Diagnosis of bile duct cancer by bile cytology: usefulness of post-brushing biliary lavage fluid - Sugimoto, Shinya; Matsubayashi, Hiroyuki; Kimura, Hirokazu; Sasaki, Keiko; Nagata, Kaori; Ohno, Sachiyo; Uesaka, Katsuhiko; Mori, Keita; Imai, Kenichiro; Hotta, Kinichi; Takizawa, Kohei; Kakushima, Naomi; Tanaka, Masaki; Kawata, Noboru; Ono, Hiroyuki (Endoscopy International Open, 2015)
Background: Pathologic evidence of biliary diseases can be obtained from cytology in addition to endoscopic retrograde cholangiopancreatography (ERCP); however, the diagnostic effectiveness is not satisfactory.Study aim: This retrospective, single-center study evaluated the efficacy of various sampling methods for the cytologic diagnosis of bile duct cancer.Patients and methods: Biliary samples included bile that was simply aspirated, brush smear, brush-rinsed saline, and post-brushing biliary lavage fluid. A set of samples was compared for cytologic efficacy in 76 patients with surgically proven bile duct cancer and in 50 patients with benign biliary stricture.Results: The cytologic sensitivity for diagnosing biliary cancer was 34 % with aspirated bile, 32 % with brush smear, 43 % with brush-rinsed saline, and 70 % with post-brushing biliary lavage fluid, in contrast to the null false-positive result in the benign cases. The sensitivity of cytology was significantly higher with post-brushing lavage fluid than with the other three sampling methods (P < 0.0001), and post-brushing lavage fluid improved the cumulative sensitivity by 24 % (P = 0.002). The sensitivity of biliary cytology was also associated with the amount of aspirated bile (P = 0.01) and with the aspiration site (P = 0.03). The rate of cancer positivity in a cytology set differed according to the tumor macroscopic type (85 % in the protruding type vs. 40 % in the flat type; P = 0.003), and according to the size of the cancer (87 % for tumors ≥ 50 mm vs. 66 % for tumors < 50 mm; P = 0.02).Conclusions: Post-brushing biliary lavage fluid cytology provides superior diagnostic efficacy, and its addition to ERCP procedures is recommended for obtaining cytologic evidence of bile duct cancer.